2017
DOI: 10.1513/annalsats.201609-727oc
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Equipoise and Shared Decision-making in Pulmonary Nodule Management. A Survey of American Thoracic Society Clinicians

Abstract: Consistent with guideline recommendations, clinicians embrace multiple options for pulmonary nodule evaluation and many are open to shared decision-making. Clinicians support the need for randomized clinical trials to strengthen the evidence for nodule evaluation, which will further improve decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Future work should also strive to gain an understanding of whether surgeon preferences regarding their and their patients’ roles in decision making vary over the course of a surgeon’s career. One may speculate that surgeons prefer to be more directive in patient counseling as their careers and level of experience progress, but there has been limited investigation into whether such a trend exists [ 50 ]. A more robust understanding of surgeon preferences would aid in the development of clinical counseling training programs for junior surgeons and trainees as well as continuing medical education programs for senior surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should also strive to gain an understanding of whether surgeon preferences regarding their and their patients’ roles in decision making vary over the course of a surgeon’s career. One may speculate that surgeons prefer to be more directive in patient counseling as their careers and level of experience progress, but there has been limited investigation into whether such a trend exists [ 50 ]. A more robust understanding of surgeon preferences would aid in the development of clinical counseling training programs for junior surgeons and trainees as well as continuing medical education programs for senior surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported that radiologist's diagnosis as a means for predicting malignancy in pulmonary nodules is more accurate than nodule classification models (29,30). However, this does not mean that the models are limited use.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral pulmonary lesions have become one of the major incidental findings during lung screening by computed tomography (CT) . A survey of American Thoracic Society Clinicians of pulmonary nodule management showed that the number of clinicians that recommended surgical resection as appropriate increased with cancer risk . There are several methods to localize the nodules before diagnostic surgery, especially for impalpable or ground glass opacities.…”
Section: Introductionmentioning
confidence: 99%